How do risks and benefits affect user’ privacy decisions? An event-related potential study on privacy calculus process - Fu, Jialin; Zhang, Jiaming; Li, Xihang (Frontiers in Psychology, 2023)
Purpose The purpose of this study is to examine how risks and benefits affect users’ privacy-related decision-making processes. Design/methods/approach This study collected and analyzed the neural activity processes of users’ privacy-related decisions when faced with personalized services with different risks and benefits through an ERP experiment that included 40 participants. Findings/results The findings show that users subconsciously categorize personalized services based on benefit; Privacy calculus affects privacy decision by influencing the allocation of cognitive resources for personalized service, and the scarcity of cognitive resources increases the degree of privacy disclosure; Emotional change in privacy decision is the result of many factors, not the result of privacy risk alone. Originality/Discussion This study provides a new perspective to explain the process of privacy decision-making, and a new approach to investigate the privacy paradox.